Development and Impact of a Handbook for Urban Sustainability Teaching in Three Chilean Universities - Ladrón de Guevara, Kay Bergamini (2024)
Since active learning of Urban Sustainability (US) represents an area in growing development, contributing to this corpus with new concrete experiences, particularly those from the Global South, is necessary. This article aims to systematize the pilot implementation of an US learning manual in Chilean higher education institutions that emerged from the Urban Explorations: Sustainable Territory course taught at the Pontificia Universidad Católica. Therefore, the authors carried out a qualitative research based on content analysis that used a theoretical-applied methodological process: first, a survey was carried out on former students of the pioneer course considering 5 parameters: contents, teaching organization, teaching methodologies, evaluation – -feedback, and relationship between students – teaching staff. Then, based on the results of the survey, a handbook with didactic activities for the US was generated, and reviewed in a focus group with former students, professors at these universities, and expert peers. Subsequently, this manual was implemented in the course at 3 Chilean universities in a mixed way (on an online platform and some face-to-face activities) in 2022, and, in the end, it was evaluated in a new focus group carried out by the professors who taught the course. The first result corresponds to the survey where a high satisfaction with the course was observed in the 5 parameters evaluated (<70%). The second result is the analysis of the focus groups that used the same 5 parameters from the first revision of the handbook and in its final version. Finally, the authors discussed the idea that this project allows to approach the teaching of US in different Chilean territorial contexts from multiple perspectives, which highlights common interests that can serve for other Latin American educational centers to use this teaching material for higher education available online for free download in Spanish.